The Effect of Inherent Supervision and Work Environment on Employee Work Discipline at the Manado State University Head Office - Lombok, Anita Sonya; Masengi, Evie; Pangkey, Itje (Technium Social Sciences Journal, 2021)
This research was conducted to know the effect of inherent supervision and the work environment partially and simultaneously on the work discipline of employees at Unima Headquarters. The research uses a quantitative approach with survey methods. The population is all employees at Unima Headquarters, totalling 149 employees spread over three bureaus. In comparison, the sampling technique is proportional random sampling with the sample size determined by the Slovin rule and obtained as many as 109 employees. The data collection technique is a questionnaire that has been tested for validity and reliability. Data analysis is multiple regression analysis through the help of the SPS program. The results of the study reveal that (1) inherent supervision has a positive and significant effect on employee work discipline at Unima Head Office, (2) work environment has a positive and significant effect on employee work discipline at Unima Headquarters, (3) inherent supervision and work environment simultaneously positive and significant effect on employee work discipline at Unima Head Office. For this reason, it is recommended that (1) Everyday employee reports must be accountable to superiors at least every week, as a form of indirect inherent supervision, (2). Sanctions for disciplinary violations must be applied consistently and fairly. Likewise, rewards need to be given to employees who are disciplined in carrying out their duties and work because doing so will maintain the attitude (Discipline) of the employee concerned and motivate other employees (undisciplined employees) to be disciplined (3). The work environment needs to be organized neat, clean, healthy, and comfortable by arranging it every day before entering work in the morning and after work in the afternoon through assigned employees (CS).